TikTok sebagai Media Pemasaran: Influencer Marketing dan E-WOM Pengaruhi Keputusan Pembelian Skincare - Nurul Qurrotul Aini; Arief Noviarakhman Zagladi (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study examines the influence of the influencer marketing and e-WOM in TikTok to Purchase decisions of skincare Product. Research/Methodology: This study uses quantitative approach with data collection through online questionnaire distribution to 100 consumers who actively use TikTok. The collected data was analyzed with the assistance of the SmartPLS4 through the inner and outer model testing processes. Results: Influencer marketing and e-WOM has significant and positive effect to skincare product purchase decisions. Conclusions: Skincare business actors can utilize TikTok as an effective and efficient marketing medium to reach a wider market. By collaborating with influential, knowledgeable, and experienced influencers, and by maximizing the spread of positive e-WOM while minimizing the spread of negative e-WOM, it can positively influence consumer purchasing decisions. Limitations: This study has limitations concering the sample size utilized. With a limited sample, the finding may not fully represent the behavior of the entire population of TikTok users or skincare consumers in general. Contribution: This study enriches the literature on digital marketing through influencer and e-WOM, also provides insights for skincare businesses, especially local brands, in developing effective and efficient strategies by leveraging TikTok to attract both domestic and international consumers.